Prospects for Gamma-Ray Emission from Magnetar Regions in CTAO Observations - M. F. Sousa; R. Costa Jr.; Jaziel G. Coelho; R. C. Dos Anjos (The Astrophysical Journal)
Recent multiwavelength observations have highlighted magnetars as significant sources of cosmic rays, particularly through their gamma-ray emissions. This study examines three magnetar regions—CXOU J171405.7–31031, Swift J1834−0846, and SGR 1806−20—known for emitting detectable electromagnetic signals. We assess the detectability of these regions using the upcoming Cherenkov Telescope Array Observatory (CTAO) by conducting an ON/OFF spectral analysis and compare the expected results with existing observations. Our findings indicate that CTAO will detect gamma-ray emissions from these three magnetar regions with significantly reduced emission flux errors compared to current instruments. In particular, the study shows that the CXOUJ1714−3810 and SwiftJ1834−0846 magnetar regions can be observed by the full southern and northern CTAO arrays in just 5 hr of observation, with mean significances above 10 σ and 30 σ , respectively. This paper discusses the regions analyzed, presents key results, and concludes with insights drawn from the study.